The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s10644-022-09421-4
|View full text |Cite
|
Sign up to set email alerts
|

Does foreign direct investment matter for environmental innovation in African economies?

Abstract: This study investigates the role of foreign direct investment (FDI) in environmental innovation in Africa during 1990–2019. It utilizes the endogenous growth theory to specify an innovation production function, estimated using the seemingly unrelated regression (SURE) method. The study employs four indicators of environmental innovation and also controls for the influence of resource abundance. Key findings from the study show evidence that FDI inflow enhances environmental innovation practices by improving re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…Further, this outcome is in harmony with the study by Awodumi (2023). He suggested that FDI in uences positive energy intensity, minimizing carbon emissions and enhancing economic growth (Awodumi, 2023) Ultimately, the discoveries demonstrate that FDI moderates the direct relationship between (1) GDP and eco-innovation and (2) ecoinnovation and carbon emissions. As a result, the mediating effect between GDP and carbon emissions differs for MENA countries with varying levels of FDI.…”
Section: Modelsupporting
confidence: 70%
See 1 more Smart Citation
“…Further, this outcome is in harmony with the study by Awodumi (2023). He suggested that FDI in uences positive energy intensity, minimizing carbon emissions and enhancing economic growth (Awodumi, 2023) Ultimately, the discoveries demonstrate that FDI moderates the direct relationship between (1) GDP and eco-innovation and (2) ecoinnovation and carbon emissions. As a result, the mediating effect between GDP and carbon emissions differs for MENA countries with varying levels of FDI.…”
Section: Modelsupporting
confidence: 70%
“…As a result, this proves that FDI can signi cantly reinforce the GDP-eco-innovation nexus to reducing carbon emissions. Further, this outcome is in harmony with the study by Awodumi (2023). He suggested that FDI in uences positive energy intensity, minimizing carbon emissions and enhancing economic growth (Awodumi, 2023) Ultimately, the discoveries demonstrate that FDI moderates the direct relationship between (1) GDP and eco-innovation and (2) ecoinnovation and carbon emissions.…”
Section: Modelsupporting
confidence: 70%
“…Further, this outcome is consistent with the study by Awodumi (2022). He suggested that FDI influences positive energy intensity, minimizing carbon emissions and enhancing economic growth (Awodumi 2023). Huang et al (2022) showed economic growth and regulation systems negatively influence the effects of FDI on carbon emissions (Huang et al 2022).…”
Section: The Dual Mediating Effect Of Fdimentioning
confidence: 99%
“…Under this scenario, green innovation is considered in the literature as one of the most important concepts that can help manufacturing companies reduce future difficulties through the development of greener and less polluting manufacturing operations (Zhao et al, 2022;Hu et al, 2023;Silva et al, 2023). Particularly, because only by changing the current production processes and systems and promoting the adoption and implementation of green innovation in all manufacturing companies, it is possible to truly achieve green development in the global economy (Zheng et al, 2023;Awodumi, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, because only by changing the current production processes and systems and promoting the adoption and implementation of green innovation in all manufacturing companies, it is possible to truly achieve green development in the global economy (Zheng et al. , 2023; Awodumi, 2023).…”
Section: Introductionmentioning
confidence: 99%